MODEL STIFFNESS VERIFICATION OF MINI-TRUCK BODY BASED ON LIGHTWEIGHT IMPROVEMENT - ZHAO HaiJun; WANG GuoHua; TIAN LiPing; LI Qi; LIU HongXia; WANG Nan (Jixie qiangdu)
Body improvement of lightweight mini-truck made vehicle mass reduction of 10. 9kg. After constraints and forces is carried out to calculate the bending stiffness and torsional stiffness around the vehicle in the pre-processing software of the finite element to model,in the contrast,it is found that the bending stiffness fell 1. 28 percent,and 2. 49 percent decline after the torsional stiffness,so they are down slightly. Tests of mini-truck is done on the real enhanced road,it is good performance.